SYNTHESISOF TETRA-p-PROPENYLTETRAESTERCALlX[4]ARENE AND TETRA-p- PROPENYLTETRACARBOXYLICACIDCALlX[4]ARENE FROMp-t-BUTYLPHENOL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
ABSTRACT A research has been conducted to synthesize tetra-p-propenyltetraestercalix{4]areneand tetra-ppropenyltetracarboxylicacidcalix[ 4] arene using p-t-butylpheriol as a starting material. The synthesis was carried out in following stages, i.e (1) synthesis of p-t-butylcalix[4]arene from p-t-butylphenol, (2) debutylation of p~tbutylcalix{ 4]arene, (3) tetraallilation of 25,26,27,28-tetrahydroxycalix{4]arene with NaH and aJ/ilbromida in dry tetrahydrofuran, (4) Claissen rearrangement of 25, 26,27, 28-tetrapropenyloxycalix[4]arene, (5) esterification of tetrap-propenyltetrahydroxycalix[4]arene, (6) hydrolisis of tetra-p-propenyltetraestercalix{4]arene. The all structures of products were observed by means of melting point, FTIR, and 1H-NMR spectrometers. Tetra-ppropenyltetraestercalix[ 4]arene compound was obtained as yellow liquid product in 55.08% yield. Tetra- p-propenyltetracarboxylicacidcalix{ 4]arene compound was obtained as white solid product with the melting point 135-137 °C at decomposedand in 70.05%yield.